Oral Mucositis in Cancer Care: Current Insights and Future Directions from a Systematic Review - Jha, Deepak Kumar; Manasa, S.; Cyriac, Kusu Susan; Shree R, Raveena (International Journal of Pharmaceutical Investigation, 2025)
Oral Mucositis (OM) is a painful inflammation often resulting from cancer therapies like chemotherapy and radiotherapy. OM manifests as ulcers that can make eating and speaking difficult and increase infection risk. Current management primarily involves clinical assessment and patient reports, but biomarker discovery is underway to improve diagnostic accuracy and treatment monitoring. Emerging biomarkers associated with inflammation, oxidative stress, and tissue repair could help assess OM severity and therapeutic efficacy. Emerging treatments for OM focus on cell-based therapies, like mesenchymal stem cells, exosomes derived from MSCs, epithelial stem cells, HSCs, and immune cell therapies that offer anti-inflammatory benefits and promote tissue repair, potentially accelerating mucosal healing. Platelet lysate, rich in growth factors, has shown promise in reducing inflammation and aiding regeneration, especially in formulations such as in situ gelling sprays. These advancing personalized treatment approaches, potentially reducing complications, aim to improve patient outcomes by enhancing healing, reducing pain, and lowering infection risk.
Keywords: Biomarkers; Cell-based therapies; Chemotherapy; Healing; Immune cells; Inflammation; Oral Mucositis; Radiotherapy